Revitalisasi Taman Baca Masyarakat (TBM) Gandasari Sebagai Strategi Pengembangan Minat Baca Anak Desa Sukaraya - Safitri, Inayah; Edora, Edora; Wibiwirutami, Trias; Nurmalia, Nurmalia (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
The low reading interest of children in Sukaraya Village is a significant problem influenced by limited access to engaging reading materials and a lack of adequate literacy facilities. This community service activity aims to revitalize the Gandasari Community Reading Park (TBM) as a strategy to develop children's reading interest in Sukaraya Village. The program was implemented through three stages: (1) preparation, (2) implementation, and (3) evaluation. The results of the activity showed a significant increase in children's reading interest, reflected in increased visits to the TBM, participation in literacy activities, and the realization of better and more sustainable TBM management. Thus, the revitalization of the Gandasari TBM has proven effective as a strategy to foster a reading culture in Sukaraya Village while simultaneously supporting the improvement of the quality of non-formal education in the community.